Use of O3 Trial Feed to Reduce Omega-6:3 Ratio in PRRS-Virus Challenged Nursery Pigs - Jenna J. Bromm; Mike D. Tokach; Jason C. Woodworth; Robert D. Goodband; Joel M DeRouchey; Chad W. Hastad; Zach B. Post; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2021)
A total of 1,056 pigs (PIC TR4 × (Fast LW × PIC L02)), originating from an active PRRSV-positive sow farm, were used in a 46-d study to evaluate growth performance of nursery pigs fed diets containing increasing levels of O3 Trial Feed, a source of omega-3 fatty acids (alpha-linolenic acid). At placement in the nursery, pens of pigs were randomly assigned 1 of 4 dietary treatments with 22 pigs per pen and 12 replications per treatment. Treatments were arranged in a completely randomized design. Dietary treatments included increasing levels of O3 Trial Feed (0, 0.75, 1.5, and 3%) with pigs remaining on treatments throughout the 4 dietary phases over the 46-d study. Overall, pigs fed increased O3 Trial Feed had increased (linear,P<0.001) ADG and ADFI and improved (linear,P<0.001) F/G. Pigs fed increasing O3 Trial Feed also had decreased (linear,P= 0.027) total removals and mortalities. In summary, O3 Trial Feed improved growth performance and reduced mortality in PRRSV-positive nursery pigs.
Keywords: Omega-3; PRRS; nursery pigs